The echo - Walters, Minette (G.P. Putnam's Sons, 1997)
A homeless man has been found dead of starvation--huddled next to a food-filled freezer--in a London socialite's garage. When journalist Michael Deacon interviews the wealthy woman, he suspects she is hiding something.